El evangelio de Jesucristo y el Imperio Romano - Aguirre Monasterio, Rafael (Estudios eclesiásticos, 2011)
The Roman Empire is considered as a global (political, social, economic, cultural) theologically legitimated system. All of the NT writings are conditioned by that context. This article begins by studying the critical component of Kingdom of God and the alternative values which it proposes. The Jesus’ answer in the Imperial Tax episode (Mt 17: 24f) is analyzed with the help from the hidden transcripts and disguised language model. Disguised language is one of the oppressed people’s resources. Paul did a strong claim of the cross and in its name promoted new and alternative social relations. Post-Pauline Tradition, Revelation, and 1 Peter took different positions on the Empire. Preventing anachronisms, Christianity in its origins offers crucial references to make discernment about Christianity – Politics relationship.